Evidence of Non-Linear Relationship Between the Electrical Conductivity of Y2O3-Stabilized-ZrO2 in the Low Temperature Range - Zhao, Wei; Jin Kim, Ik; Gong, Jianghong (Asian Journal of Chemistry, 2010)
The relationship between the electrical conductivity and temperature of Y2O3-Stabilized-ZrO2 (YSZ) electrolyte samples in the lower temperature range was examined by complex impedance measurements at temperatures between 363 and 733 K. There was a non-linear relationship between the electrical conductivity and temperature. The former decreased gradually at a decreasing rate with decreasing temperature. This paper presents evidence supporting these results.